A framework for understanding multisectoral collaboration in selected public high schools - Caoile, Patrick De Vera (Animo Repository, 2013)
Multisectoral collaboration (MSC) is another novel approach to pursue projects, involving health, infrastructure development, environment and education, combining the private and public sector with civil society. The framework of Eisenhardt (1989) was used to build a road map and contribute to a positioning theory evaluating the six public high schools in Mandaluyong City, using the eight steps of Eisenhardt (1989) that resulted in six emergent frameworks and five propositions on the nature of MSC, its causal condition, contextual condition, actions and strategies and expected outcomes and consequences. The five propositions and six emergent frameworks are triangulated with extant literature to create a MSC framework that is robust and elegant, formulated with parsimony, testability and logical coherence.